The Effect of Fasting Pattern on Biological Performance of Quail at Early Production Period - Tugiyanti, Efka (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
The objective of this research was to find out the effect of fasting pattern on biological performance of quail at early production period. 50 kg commercial feed, vitamins and medicine were applied on 140 heads of seven old day quail. Four different fasting pattern were employed as treatment, i.e. ad libitum diet (Po); every two days fasting (P1); every three days fasting (P2); every four days fasting (P3); and every five days fasting (P4). Ad libitum amount of corn and water were offered to the fasted quail. Completely Randomized Design (CRD) was chosen as research design. An Honestly Significant Different (HSD) test was applied to analyze the difference among treatments. Results showed that fasting pattern at early growth period had significant influence on body weight at 35 days of age and at sexual maturity (P<0.01); weight of reproduction organ (P<0.05) and age of sexual maturity (P<0.05). It was concluded that fasting pattern had influence on biological performance of quail at early production. Quail with no fasting (ad libitum diet) had the same biological performance as quails with 5 days of fasting. (Animal Production 7(3): 185-188 (2005) Key Words: Quail, Fasting Pattern, Biological Performance